Diagnostic Imaging Management System in Batu Pahat Hospital - Abdullah, Nuraini; Selamat, Norhanim; Kasim, Shahreen (International Journal of Advanced Science Computing and Engineering, 2019)
Â Management System Development Department of Diagnostic Imagingat Hospital Batu Pahat is an effort to automate the existing manualsystem which includes the application of radiological, patientinformation storage, information storage staff, patient follow-upappointments, patient and personal property items stored equipmentinformation manually. Storage of records in this manual will result induplication of information if the patient came to do the x-ray followup.In addition, all patients who undergoing treatment radiological arerequired to leave their personal belongings outside the treatment room.This is likely the patient will lose personal items is high. The mainpurpose of this system to ensure the Diagnostic Imaging Departmentof Hospital Batu Pahat in upgrading and improving its serviceperformance. Prototype Model development methodology used in thisproject. The system will help facilitate the management of dailyoperations of the Department of Diagnostic Imaging. As a result ofthis project is expected to assist the Department of Diagnostic Imagingtowards more efficient management of the organization, in line withgovernment efforts to provide the best service to the people.